Influential Factors on Delay Marriage in Tehran - Saadati , Mahsa; Bagheri, Arezoo (Sigma&Mu: Journal of Mathematics, Statistics and Data Science, 2023)
Today, youth’s marriage due to the socio-economic conditions has become one of the most important subjects in social science. The purpose of this article was to investigate the factors affecting delay marriage of married men and women in Tehran. In this study, the information of 612 married women aged 15-49 years and 588 married men aged 20-59 years were collected through structured questionnaire using two-stage stratified sampling method from different regions of Tehran in 2017, and data were analyzed by Logistic regression model. About 15.3% of people believed that they had delay marriage. The results of logistic regression model showed that, by increasing age, the odds of delay marriage is decreased; employed and migrant people, and those who had less than 2 million Tomans of household expenditure in a month, compared to unemployed (OR = 0.542) and non-migrant (OR = 0.509) people and those who liv in households with more than 3.5 million Tomans expenditure in a month (OR = 0.512) are less likely to delay marriage. However, Fars people and those with kinship marriages were more likely to delay marriage than other ethnicities (OR =1.830) and non-kinship marriages (OR =1.693), respectively. According to the results, job status and expenditure are two influential factors on the delay in marriage age; policymakers in this field can reduce this delay by providing a right platform for working which causes youths earn enough income and can start their marriage life.